Anesthetic Management for Laser Excision of Ball-Valving Laryngeal Masses - Benjamin B. Bruins; Natasha Mirza; Ernest Gomez; Joshua H. Atkins (Case Reports in Anesthesiology)
A 47-year-old obese woman with GERD and COPD presents for CO2-laser excision of bilateral vocal fold masses. She had a history of progressive hoarseness and difficulty in breathing. Nasopharyngeal laryngoscopy revealed large, mobile, bilateral vocal cord polyps that demonstrated dynamic occlusion of the glottis. We describe the airway and anesthetic management of this patient with a topicalized C-MAC video laryngoscopic intubation using a 4.5 mm Xomed Laser Shield II endotracheal tube. We examine the challenges of anesthetic management unique to the combined circumstances of a ball-valve lesion and the need for a narrow-bore laser compatible endotracheal tube.